INFLUÊNCIA DO SISTEMA DE PRODUÇÃO NA QUALIDADE PÓS-COLHEITA DE ALFACE - VETRUVE, Italo Ferreira; RIBEIRO, Fernanda Cristina; TENÓRIO, Joaquim Neto; OLIVEIRA, Vitor Garcia de; BERTOLO, Diego Miguel Blanco (ANAIS DO ENIC, 2025)
-